(untitled) (World Economics and Finance Bulletin, 2024)
The investigation intended to know the importance of financial accounting standards in decreasing the effects of disasters and crises (Corona pandemic) on financial statements in institutions by utilizing them in the public sector. The researcher employed the descriptive analytical method to describe the phenomenon under investigation, as well as the questionnaire to collect the findings of the analytical study, along with the statistical analysis software. Among the most significant findings of the researcher is the lack of legitimacy of the information published in financial accounting and control reports, this information has a flaw that causes the failure to apply accounting rules in public sector institutions, as a result, there are numerous crises and disasters that are difficult to address later. According to the intended plans, there is a lack of productivity due to the lack of qualification and training for employees, and there are no definitive rules regarding the evaluation of employees, this negatively affects their productivity. No modern specializations exist to correct mistakes or Deviations at the time and address them in the most effective way possible at the appropriate time. The researcher suggests that the proper way to select workers is to consider the plans already in place and the CV, which must have the required abilities, to employ workers based on their scientific and practical qualifications, and to reduce the frequency of crises and disasters that institutions are susceptible to during the course of employment. This positively affects the financial reports of transparent nature, which are intended to improve performance, thus achieving the goals of the establishment and providing modern devices that keep pace with development and good tools that assist the internal control system and enhance it to promote the concerned institutions’ work and support it